Composite solid electrolyte membrane, preparation method thereof and solid-state battery

By pressing the first and second solid electrolyte raw materials into the composite substrate layer, the interface problems and poor density of the traditional composite solid electrolyte membrane are solved, and the ionic conductivity and cycling performance of the lithium-ion battery are improved.

CN119253080APending Publication Date: 2025-01-03SUZHOU QINGTAO NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411417679.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

There are interface problems and poor density during the preparation process of traditional composite solid electrolyte membranes, which affect the performance of lithium-ion batteries.

Method used

By using the composite substrate layer method, the first substrate layer and the second substrate layer are laminated, and the first and second solid electrolyte raw materials are respectively pressed into the respective porous structures, and a mixed layer is formed by the action of pressure and temperature. Improve density and ionic conductivity.

Benefits of technology

It effectively improves the interface problems of the composite solid electrolyte membrane, improves ionic conductivity and density, reduces the internal resistance and capacity loss of the battery, and improves cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253080A_ABST
    Figure CN119253080A_ABST
Patent Text Reader

Abstract

The invention relates to a composite solid electrolyte membrane, a preparation method thereof and a solid-state battery. The preparation method comprises the following steps: stacking the first base material layer and the second base material layer to prepare the composite base material layer; wherein the first base material layer and the second base material layer are both of a porous structure, and the porosity of the first base material layer is smaller than that of the second base material layer; pressing a second solid electrolyte raw material into the porous structure of the second base material layer; wherein the second solid electrolyte raw material comprises a second solid electrolyte; pressing a first solid electrolyte raw material into the porous structure of the first base material layer on one side, far away from the second base material layer, of the first base material layer to prepare a composite solid electrolyte membrane; wherein the first solid electrolyte raw material comprises a first solid electrolyte. According to the preparation method of the composite solid electrolyte membrane provided by the invention, the porosity of the composite solid electrolyte membrane is reduced, the ionic conductivity of the composite solid electrolyte membrane is improved, the internal resistance of the battery is reduced, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a composite solid electrolyte membrane and a preparation method thereof, and a solid-state battery. Background Art

[0002] In recent years, due to the increasing requirements for the safety performance of lithium-ion batteries, solid electrolytes are mostly used in existing production to replace liquid electrolytes.

[0003] Since traditional halide solid electrolytes have the characteristics of high ion conductivity but low resistance to reduction, the traditional process is to stack a layer of halide solid electrolyte membrane that is more resistant to reduction on the surface of the halide solid electrolyte membrane to improve the comprehensive performance of the halide solid electrolyte membrane. However, this method usually prepares the solid electrolyte layer separately and then stacks and presses it. The composite solid electrolyte membrane prepared in this way has certain interface problems, which is not conducive to reducing the internal resistance of the battery. Moreover, the density of the composite solid electrolyte membrane is also relatively poor.

[0004] Therefore, there is an urgent need to improve the traditional preparation process to optimize the comprehensive performance of the composite solid electrolyte membrane. Summary of the invention

[0005] Based on this, it is necessary to provide a composite solid electrolyte membrane and a preparation method thereof and a solid-state battery to solve the above technical problems.

[0006] The first aspect of the present application provides a method for preparing a composite solid electrolyte membrane, which comprises the following steps: stacking a first substrate layer and a second substrate layer to prepare a composite substrate layer; wherein the first substrate layer and the second substrate layer are both porous structures, and the porosity of the first substrate layer is less than that of the second substrate layer; pressing a second solid electrolyte raw material into the porous structure of the second substrate layer; wherein the second solid electrolyte raw material includes a second solid electrolyte; on a side of the first substrate layer away from the second substrate layer, pressing the first solid electrolyte raw material into the porous structure of the first substrate layer to prepare a composite solid electrolyte membrane; wherein the first solid electrolyte raw material includes a first solid electrolyte.

[0007] In some embodiments, in the step of stacking the first substrate layer and the second substrate layer, the first substrate layer having a porosity of 50% to 85% and the second substrate layer having a porosity of 70% to 95% are stacked.

[0008] Preferably, the second substrate layer is laminated on the first substrate layer by spinning, or the first substrate layer is laminated on the second substrate layer by spinning.

[0009] In some embodiments, the step of pressing the second solid electrolyte raw material into the porous structure of the second substrate layer specifically includes: spraying the second solid electrolyte raw material on the surface of the second substrate layer and filling it.

[0010] In some embodiments, the filling is performed by vibrating the composite substrate layer using a vibrating screen; or, the filling is performed by lightly pressing one side of the composite substrate layer sprayed with the second solid electrolyte raw material using a sponge roller.

[0011] In some embodiments, before the step of pressing the second solid electrolyte raw material into the porous structure of the second substrate layer, the step further includes: mixing the second solid electrolyte with a fiberizable binder and fiberizing the mixture to prepare the second solid electrolyte raw material.

[0012] Preferably, the second solid electrolyte and the fiberizable binder are mixed in a mass ratio of (99:1) to (99.9:0.1).

[0013] In some embodiments, before the step of pressing the first solid electrolyte raw material into the porous structure of the first substrate layer, the step further includes: turning over the composite substrate layer.

[0014] In some embodiments, the step of pressing the first solid electrolyte raw material into the porous structure of the first substrate layer specifically includes: spraying the first solid electrolyte raw material on the surface of the first substrate layer and filling it.

[0015] Preferably, a sponge roller is used to roll the composite substrate layer on one side sprayed with the first solid electrolyte raw material for filling; the rolling pressure is 0.01 MPa to 5 MPa.

[0016] Preferably, the particle size D50 of the first solid electrolyte is 1 μm to 5 μm.

[0017] In some embodiments, the step of pressing the second solid electrolyte raw material into the porous structure of the second substrate layer specifically includes: applying a pressing force to the surface of the composite substrate layer sprayed with the second solid electrolyte raw material, the pressing pressure is 2t to 3t; the pressing time is 30s to 5min; the pressing temperature is 60℃ to 100℃.

[0018] In some embodiments, the step of pressing the first solid electrolyte raw material into the porous structure of the first substrate layer specifically includes: applying a pressing force to the surface of the composite substrate layer sprayed with the first solid electrolyte raw material, the pressing pressure is 2t to 3t; the pressing time is 30s to 5min; the pressing temperature is 60℃ to 100℃.

[0019] The second aspect of the present application provides a composite solid electrolyte membrane, which is prepared by the preparation method provided by the first aspect.

[0020] A third aspect of the present application provides a solid-state battery, which includes a positive electrode, a negative electrode and the composite solid electrolyte membrane provided in the second aspect.

[0021] Preferably, the first substrate layer faces the positive electrode of the electrochemical device, the second substrate layer faces the negative electrode of the electrochemical device, and the second solid electrolyte has better reduction resistance than the first solid electrolyte.

[0022] Compared with the traditional technology, this application has at least the following beneficial effects:

[0023] The preparation method of the composite solid electrolyte membrane provided by the present application adopts a composite substrate layer, and the second solid electrolyte raw material and the first solid electrolyte raw material are respectively pressed into the second substrate layer and the first substrate layer in the composite substrate layer, and the first solid electrolyte raw material and the second solid electrolyte raw material are in contact under pressure, which makes it easier to form a mixed layer. Therefore, the interface problem of the composite solid electrolyte membrane can be effectively improved, and it can also effectively avoid that when the two solid electrolyte layers are pressed, it is easy to form a void area due to poor contact, which affects the lithium ion transmission. The ionic conductivity of the composite solid electrolyte membrane prepared by the present application is improved.

[0024] On the other hand, by setting the porosity of the first substrate layer smaller than that of the second substrate layer, it plays a supporting role when the second solid electrolyte raw material is pressed into the second substrate layer, which can effectively improve the density of the filled second substrate layer; the filled second substrate layer can also play a supporting role when the first solid electrolyte raw material is pressed into the first substrate layer, thereby effectively improving the density of the composite solid electrolyte membrane.

[0025] Therefore, the preparation method of the composite solid electrolyte membrane of the present application improves the density of the composite solid electrolyte membrane, reduces internal defects, reduces the internal resistance of the battery, forms a continuous ion channel in the process of pressing the solid electrolyte raw material, improves the ionic conductivity of the composite solid electrolyte membrane, reduces the capacity loss of the battery during the charge and discharge process, and thus improves the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of a process for preparing a composite solid electrolyte membrane in one embodiment of the present application. DETAILED DESCRIPTION

[0027] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0028] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features, and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0029] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0030] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0031] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0033] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0035] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0036] The first aspect of the present application provides a method for preparing a composite solid electrolyte membrane, such as Figure 1 As shown, the preparation method comprises the following steps:

[0037] S1. Stacking a first substrate layer and a second substrate layer to prepare a composite substrate layer.

[0038] The first substrate layer and the second substrate layer are both porous structures, and the porosity of the first substrate layer is smaller than the porosity of the second substrate layer.

[0039] S2. Pressing the second solid electrolyte raw material into the porous structure of the second substrate layer.

[0040] Wherein, the second solid electrolyte raw material includes a second solid electrolyte.

[0041] S3. On a side of the first substrate layer away from the second substrate layer, press the first solid electrolyte raw material into the porous structure of the first substrate layer to prepare a composite solid electrolyte membrane.

[0042] Wherein, the first solid electrolyte raw material includes a first solid electrolyte.

[0043] The preparation method of the composite solid electrolyte membrane provided by the present application adopts a composite substrate layer, and the second solid electrolyte raw material and the first solid electrolyte raw material are respectively pressed into the second substrate layer and the first substrate layer in the composite substrate layer, and the first solid electrolyte raw material and the second solid electrolyte raw material are in contact under pressure, which makes it easier to form a mixed layer. Therefore, the interface problem of the composite solid electrolyte membrane can be effectively improved, and it can also effectively avoid that when the two solid electrolyte layers are pressed, it is easy to form a void area due to poor contact, which affects the lithium ion transmission. The ionic conductivity of the composite solid electrolyte membrane prepared by the present application is improved.

[0044] On the other hand, by setting the porosity of the first substrate layer smaller than that of the second substrate layer, it plays a supporting role when the second solid electrolyte raw material is pressed into the second substrate layer, which can effectively improve the density of the filled second substrate layer; the filled second substrate layer can also play a supporting role when the first solid electrolyte raw material is pressed into the first substrate layer, thereby effectively improving the density of the composite solid electrolyte membrane.

[0045] Therefore, the preparation method of the composite solid electrolyte membrane of the present application improves the density of the composite solid electrolyte membrane, reduces internal defects, reduces the internal resistance of the battery, forms a continuous ion channel in the process of pressing the solid electrolyte raw material, improves the ionic conductivity of the composite solid electrolyte membrane, reduces the capacity loss of the battery during the charge and discharge process, and thus improves the cycle performance of the battery.

[0046] In this article, "porosity" refers to the ratio of the volume occupied by internal pores to the apparent volume. The higher the porosity, the more pores there are inside the material and the lower the density.

[0047] In some embodiments, the components of the first solid electrolyte and the second solid electrolyte are the same or different, and are independently selected from one or a combination of oxide solid electrolytes, sulfide solid electrolytes, and halide solid electrolytes.

[0048] Furthermore, the first solid electrolyte and the second solid electrolyte are both halide solid electrolytes.

[0049] It is understood that halide solid electrolyte is a known electrolyte material, which is considered to have the advantages of both oxide solid electrolyte and sulfide solid electrolyte. Halide solid electrolyte can usually use Li a MX b , where M is a metal element, which can be a mixture of multiple metal elements, the multiple metals can be of the same or different valences, and X is a halogen element. The structure of metal halide electrolytes depends on their ion radius and ion arrangement. There are generally three types of halide electrolytes commonly studied: Li a MX4, Li a MX6 and Li a MX8, etc. It can be understood that the present application does not specifically limit the type of halide solid electrolyte. On the basis of not violating the inventive concept of the present application, any known halide solid electrolyte can be used in the present application. It is only used as an illustrative example rather than a limitation on the scope of protection. The halide solid electrolyte can be Li2CdCl4, Li2MgCl4, Li2CdI4, Li2ZnI4, Li2ZrCl6, Li3InCl6, Li3YCl6, Li3ErCl6, Li3ScCl6, Li3HoCl6 and combinations thereof.

[0050] In some embodiments, the first substrate layer faces the positive electrode of the electrochemical device, the second substrate layer faces the negative electrode of the electrochemical device, and the second solid electrolyte has better reduction resistance than the first solid electrolyte.

[0051] The first substrate layer is arranged toward the positive electrode of the electrochemical device, and the second substrate layer is arranged toward the negative electrode of the electrochemical device, and the second halide solid electrolyte has better reduction resistance than the first halide solid electrolyte. Since the porosity of the first substrate layer is smaller than that of the second substrate layer, the second solid electrolyte layer formed after the second solid electrolyte is pressed in is denser, which is beneficial to improving the isolation effect between the negative electrode and the first solid electrolyte, thereby improving the compatibility of the composite solid electrolyte membrane and the electrode, reducing the internal resistance of the battery, and improving the cycle performance of the battery.

[0052] In some embodiments, the first substrate layer includes one or more of aramid film, non-woven fabric, and polyimide film.

[0053] In some embodiments, the second substrate layer includes one or more of an aramid film, a non-woven fabric, and a polyimide film.

[0054] It can be understood that, without departing from the inventive concept of the present application, any known substrate with a porous structure can be used for the first substrate layer and the second substrate layer in the present application.

[0055] In some embodiments, in step S1, a first substrate layer with a porosity of 50% to 85% and a second substrate layer with a porosity of 70% to 95% are stacked.

[0056] In some embodiments, the second substrate layer is laminated on the first substrate layer by spinning.

[0057] Furthermore, the second substrate layer is formed by stacking on the first substrate layer by electrospinning, so that the porosity of the second substrate layer can be controlled by the electrospinning process.

[0058] Furthermore, a second substrate layer is formed by stacking on the first substrate layer by melt-blowing spinning. Unlike electrospinning, the raw materials prepared by melt-blowing need to pass through a nozzle that melts the polymer, and the high-temperature air promotes the deposition of spinning droplets on the cooled substrate at high speed. Compared with electrospinning, the whole process does not require an external electric field and does not require additional solvents. The thickness and density of the second substrate layer can be controlled within a reasonable range through the melt-blowing process.

[0059] In other embodiments, the first substrate layer is laminated on the second substrate layer by spinning.

[0060] Furthermore, the first substrate layer is stacked on the second substrate layer by electrospinning.

[0061] Furthermore, the first substrate layer is laminated on the second substrate layer by melt-blowing.

[0062] In some embodiments, step S2 specifically includes: spraying the second solid electrolyte raw material on the surface of the second substrate layer and filling it, so that the second solid electrolyte raw material can be evenly distributed in the second substrate layer.

[0063] In some embodiments, the filling is performed by vibrating the composite substrate layer using a vibrating screen.

[0064] In some specific embodiments, a sponge roller is used to lightly press one side of the composite substrate layer sprayed with the second solid electrolyte raw material for filling.

[0065] In some of the embodiments, step S2 specifically includes: applying a pressing force to the surface of the composite substrate layer sprayed with the second solid electrolyte raw material, the pressing pressure is 2t to 3t; the pressing time is 30s to 5min; the pressing temperature is 60°C to 100°C.

[0066] In some embodiments, before step S2, the method further includes: mixing the second solid electrolyte with a fiberizable binder and fiberizing the mixture to prepare a second solid electrolyte raw material. The fiberizable binder is added to the second solid electrolyte raw material to prevent the first substrate layer from falling off when the composite substrate layer is subsequently turned over.

[0067] Furthermore, the second solid electrolyte and the fiberizable binder are mixed in a mass ratio of (99:1) to (99.9:0.1).

[0068] As used herein, "fiberizable binder" refers to a binder that can be transformed from a granular state to a fibrous state under the action of high shear force.

[0069] In some embodiments, the fiberizable binder includes one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene (PE), and polypropylene (PP).

[0070] In some of the embodiments, before step S3, the step further includes: turning over the composite substrate layer.

[0071] In some embodiments, step S3 specifically includes: spraying the first solid electrolyte raw material on the surface of the first substrate layer and filling it, so that the first solid electrolyte raw material can be evenly distributed in the first substrate layer.

[0072] In some of the embodiments, step S3 specifically includes: applying a pressing force to the surface of the composite substrate layer sprayed with the first solid electrolyte raw material, the pressing pressure is 2t to 3t; the pressing time is 30s to 5min; and the pressing temperature is 60°C to 100°C.

[0073] In some embodiments, the filling is performed by vibrating the composite substrate layer using a vibrating screen.

[0074] In some specific embodiments, a sponge roller is used to lightly press one side of the composite substrate layer sprayed with the second solid electrolyte raw material for filling; further, the roller pressure is 0.01MPa to 5MPa, including but not limited to 0.01MPa, 0.05MPa, 0.1MPa, 0.5MPa, 1MPa, 1.5MPa, 2MPa, 2.5MPa, 3MPa, 3.5MPa, 4MPa, 4.5MPa, 5MPa. The roller pressure within the above range is conducive to ensuring the pressing strength while preventing the second solid electrolyte from being pressed out from the other side.

[0075] In some embodiments, the first solid electrolyte and the second solid electrolyte are in powder form.

[0076] In some embodiments, the particle size D50 of the first solid electrolyte is 1 μm to 5 μm, including but not limited to 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm.

[0077] The second aspect of the present application provides a composite solid electrolyte membrane, which is prepared by the preparation method provided by the first aspect.

[0078] In some embodiments, the porosity of the composite solid electrolyte membrane is 0.1% to 10%, including but not limited to 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.

[0079] A third aspect of the present application provides a solid-state battery, which includes a positive electrode, a negative electrode and the composite solid-state electrolyte membrane provided in the first aspect.

[0080] In some embodiments, the first substrate layer faces the positive electrode of the electrochemical device, the second substrate layer faces the negative electrode of the electrochemical device, and the second solid electrolyte has better reduction resistance than the first solid electrolyte.

[0081] In some embodiments, the secondary battery provided by the present invention includes a positive electrode, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer having a thickness of greater than or equal to about 1 μm to less than or equal to about 1,000 μm. The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes a compound that reversibly intercalates and deintercalates lithium ions.

[0082] In some embodiments, the positive electrode active material comprises one or more transition metal cations, such as manganese (Mn), nickel (Ni), cobalt (Co), chromium (Cr), iron (Fe), vanadium (V), and combinations thereof.

[0083] In some embodiments, the positive electrode active material is one of a layered oxide, a spinel, and a polyanion. For example, the layered oxide (e.g., a rock salt layered oxide) comprises one or more lithium-based positive electrode active materials selected from the group consisting of LiCoO2 (LCO), LiNi x Mn y Co 1-x-y O2 (where 0≤x≤1 and 0≤y≤1), LiNi 1-x-y Co x Al y O2 (where 0≤x≤1 and 0≤y≤1), LiNi x Mn 1-x O2 (where 0≤x≤1), and Li 1+x MO2 (wherein M is one of Mn, Ni, Co and Al and 0≤x≤1). The spinel comprises one or more lithium-based positive active materials selected from the group consisting of LiMn2O4 (LMO) and LiNi x Mn 1.5 O4. The olivine type contains one or more lithium-based positive electrode active materials LiMPO4 (wherein M is at least one of Fe, Ni, Co and Mn). The polyanion cation contains, for example, phosphates such as LiV2(PO4)3 and / or silicates such as LiFeSiO4.

[0084] In some embodiments, the positive electrode active material layer includes a binder, which improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material layer and the positive electrode current collector.

[0085] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.

[0086] In some embodiments of the present invention, the mass of the binder accounts for 1%-20% of the mass of the positive electrode material layer.

[0087] In some embodiments of the present invention, the positive electrode active material layer includes a conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0088] In some embodiments, the mass of the conductive agent accounts for 1%-20% of the mass of the positive electrode material layer.

[0089] In some embodiments, the positive electrode plate provided by the present invention further includes a fast ion conductor for improving the ionic conductivity of the positive electrode. The present invention does not limit the type of fast ion conductor, which can be an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a lithium salt, etc. Optionally, the mass of the fast ion conductor accounts for 1%-20% of the mass of the positive electrode plate; preferably 5%-20%.

[0090] In some embodiments, the positive electrode sheet includes a positive electrode current collector. Exemplarily, the positive electrode current collector may be aluminum (Al), but is not limited thereto.

[0091] It is understood that the above examples of positive electrode active materials, binders, and conductive materials are only illustrative, and any known positive electrode active materials, binders, and conductive materials can be used in this application without violating the inventive concept of this application. And the addition of known additives based on actual use requirements should also be considered within the scope of protection of this application.

[0092] Negative electrode:

[0093] In some embodiments of the present invention, the negative electrode sheet includes a current collector and a negative electrode active material layer disposed on the current collector.

[0094] In the present invention, the specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.

[0095] In some embodiments, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.

[0096] In some embodiments, the mass percentage of the negative electrode active material contained in the negative electrode active material layer may be 80%-99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95%-97%.

[0097] In some embodiments, the negative electrode material layer may include a binder; the binder improves bonding of negative electrode active material particles to each other and bonding of the negative electrode active material to the current collector.

[0098] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, and the like.

[0099] In some embodiments, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry, wherein the negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying, and the thickener can generally be used to adjust the viscosity of the slurry.

[0100] In some embodiments, the aforementioned viscosity enhancer may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof.

[0101] In some embodiments, the mass proportion of the thickener in the negative electrode slurry can be 0.1%-5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5%-3%, and more preferably 0.6%-2%.

[0102] In some embodiments, the negative electrode active material layer includes a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0103] In some embodiments of the present invention, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0104] Secondary battery:

[0105] In some embodiments, the secondary battery of the present invention comprises the above-mentioned positive electrode sheet, negative electrode sheet, separator, electrolyte, etc., but is not limited thereto.

[0106] In some embodiments, the secondary battery according to the present invention is made by stacking the above-mentioned positive and negative electrode sheets.

[0107] In some embodiments, the secondary battery of the present invention may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0108] In some embodiments, a method for preparing a battery is provided, comprising the following steps: aligning and stacking positive electrode sheets on one side of a first substrate layer in a composite solid electrolyte membrane, rolling, and then attaching negative electrode sheets on one side of a second substrate layer in the composite solid electrolyte membrane, and assembling to obtain a battery.

[0109] The present application will be further described below with reference to specific embodiments and comparative examples.

[0110] Example 1

[0111] Composite solid electrolyte membrane:

[0112] (1) With the first substrate layer as the base, the second substrate layer is formed on the first substrate layer by electrospinning.

[0113] Among them, the first substrate layer and the second substrate layer are both porous structures; the first substrate layer is a non-woven fabric with a porosity of 65% and a thickness of 10 μm; the second substrate layer is an aramid fiber membrane with a porosity of 85% and a thickness of 10 μm.

[0114] (2) The second solid electrolyte Li3YCl5F and the fiberizable binder PTFE are mixed and fiberized in a mass ratio of 99.5:0.5 to obtain a second solid electrolyte raw material.

[0115] (3) Pressing the second solid electrolyte raw material into the porous structure of the second substrate layer: spraying the second solid electrolyte raw material on the surface of the second substrate layer, and using a vibrating screen to vibrate the composite substrate layer for filling; applying a pressing force to the surface of the composite substrate layer sprayed with the second solid electrolyte raw material, the pressing pressure is 2 tons; the pressing time is 10 minutes; the pressing temperature is 75°C.

[0116] (4) turning over the composite substrate layer;

[0117] (5) The first halide solid electrolyte Li2ZrCl6 and the fiberizable binder PTFE are mixed and fiberized in a mass ratio of 99.5:0.5 to obtain a first solid electrolyte raw material; wherein the particle size D50 of Li2ZrCl6 is 3 μm.

[0118] (6) Pressing a first solid electrolyte raw material into the porous structure of the first substrate layer on a side of the first substrate layer away from the second substrate layer to prepare a composite solid electrolyte membrane.

[0119] The specific steps include: spraying the first solid electrolyte raw material on the surface of the first substrate layer, and using a sponge roller to roll the side of the composite substrate layer sprayed with the first solid electrolyte raw material for filling, the rolling pressure is 0.5Mpa, and the number of rolling times is 5 times; applying a pressing force to the surface of the composite substrate layer sprayed with the first solid electrolyte raw material, the pressing pressure is 2t, the pressing time is 10min, and the pressing temperature is 75°C.

[0120] Solid-state batteries:

[0121] The positive electrode sheets are aligned and stacked on one side of the first substrate layer in the composite solid electrolyte membrane, and after rolling, the negative electrode sheets are attached to the second substrate layer in the composite solid electrolyte membrane, and assembled with the shell to obtain a solid-state battery. Among them, the positive electrode composition is 95wt% NCM622, 3wt% PTFE and 2wt% super-P; the negative electrode composition is 95wt% graphite, 3wt% (CMC+SBR) and 2wt% super-P.

[0122] Example 2

[0123] The preparation method of the composite solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0124] In step (1), the porosity of the first substrate layer is 50%.

[0125] Example 3

[0126] The preparation method of the composite solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0127] In step (1), the porosity of the first substrate layer is 85%, and the porosity of the second substrate layer is 95%.

[0128] Example 4

[0129] The preparation method of the composite solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0130] In step (1), the porosity of the second substrate layer is 70%.

[0131] Example 5

[0132] The preparation method of the composite solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0133] In step (6), the pressing pressure is 3t.

[0134] Example 6

[0135] The preparation method of the composite solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0136] In step (5), the particle size D50 of Li2ZrCl6 is 5 μm.

[0137] Example 7

[0138] The preparation method of the composite solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0139] In step (5), the particle size D50 of Li2ZrCl6 is 1 μm.

[0140] Example 8

[0141] The preparation method of the composite solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0142] The first solid electrolyte is Li3InCl6; the second solid electrolyte is Li2ZrCl5O 0.5 .

[0143] Comparative Example 1

[0144] Solid electrolyte membrane:

[0145] (1) The first halide solid electrolyte Li2ZrCl6 and the fiberizable binder PTFE are mixed and fiberized, and then pressed to obtain a first solid electrolyte layer.

[0146] (2) The second solid electrolyte Li3YCl5F and the fiberizable binder PTFE are mixed and fiberized, and then pressed to obtain a second solid electrolyte layer.

[0147] (3) The first solid electrolyte layer, the substrate layer, and the second solid electrolyte layer are stacked and pressed to form a composite solid electrolyte membrane. The substrate layer is a non-woven fabric with a porosity of 65%.

[0148] Solid-state batteries:

[0149] The solid electrolyte membrane is aligned and stacked with the positive electrode sheet, and after rolling, the negative electrode sheet is attached, and after assembling with the shell, a solid-state battery is obtained. The positive electrode composition is 95wt% NCM622, 3wt% PTFE and 2wt% super-P; the negative electrode composition is 95wt% graphite, 3wt% (CMC+SBR) and 2wt% super-P.

[0150] The parameters of the embodiments and comparative examples are summarized in Table 1 below.

[0151] Table 1

[0152]

[0153]

[0154] In Table 1, “ / ” indicates that the structure or substance does not exist.

[0155] Test Case

[0156] (1) Porosity test

[0157] Using fully automatic rapid specific surface area and porosity analyzer VII 2390 The porosity of the first substrate layer, the second substrate layer, the solid electrolyte membrane and the composite solid electrolyte membrane in the embodiment and the comparative example was tested. The test results are shown in Table 1 and Table 2.

[0158] (2) Ionic conductivity test

[0159] At 25°C, the solid electrolyte membranes and composite solid electrolyte membranes obtained in Examples 1 to 8 and Comparative Example 1 adopt a test structure of stainless steel sheet / solid electrolyte membrane / stainless steel sheet, the frequency range is 0.1 Hz-7 MHz, and the AC signal amplitude Z is 10 -2The AC impedance test was carried out under the condition of 100 V, and the calculation was performed according to the ionic conductivity calculation formula σ=L / (S*R), where L is the thickness of the composite solid electrolyte membrane, S is the cross-sectional area of ​​the composite solid electrolyte membrane, and R represents the charge transfer resistance. The test results are shown in Table 2.

[0160] (3) Cyclic performance test

[0161] The solid-state batteries of Examples 1 to 8 and Comparative Example 1 were subjected to cycle tests. At a temperature of 25°C ± 2°C, the first step was to charge at 0.1C or a specified current to the final voltage, the cut-off current was 0.01C, and the battery was left standing for 30 minutes; the second step was to discharge at 0.1C to the final discharge voltage (2.75V), record the discharge capacity, and leave the battery standing for 30 minutes; the first and second steps were repeated to test the cycle performance of the solid-state battery for 100 cycles. The test results are shown in Table 2.

[0162] (4) Battery internal resistance test

[0163] The internal resistance of the solid-state batteries of Examples 1 to 8 and Comparative Example 1 was measured by a voltage internal resistance meter. The test results are shown in Table 2.

[0164] Table 2

[0165]

[0166] As shown in Table 2, by comparing Examples 1 to 8 and Comparative Example 1, it can be seen that the porosity of the composite solid electrolyte membrane provided by the present application is reduced, the ionic conductivity of the composite solid electrolyte membrane is improved, the cycle capacity retention rate of the battery is improved, and the internal resistance of the battery is reduced.

[0167] As shown in Table 2, by comparing Example 1 and Example 8, it can be seen that when the reduction resistance of the second halide solid electrolyte is better than that of the first halide solid electrolyte, the compatibility of the composite solid electrolyte membrane and the electrode is improved, thereby reducing the internal resistance of the battery.

[0168] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0169] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a composite solid electrolyte membrane, characterized in that: The following steps are involved: The first substrate layer and the second substrate layer are stacked to prepare a composite substrate layer; Wherein, both the first substrate layer and the second substrate layer are porous structures, and the porosity of the first substrate layer is smaller than the porosity of the second substrate layer; Pressing a second solid electrolyte raw material into the porous structure of the second substrate layer; Wherein, the second solid electrolyte raw material includes a second solid electrolyte; On a side of the first substrate layer away from the second substrate layer, pressing a first solid electrolyte raw material into the porous structure of the first substrate layer to prepare a composite solid electrolyte membrane; Wherein, the first solid electrolyte raw material includes a first solid electrolyte.

2. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: In the step of stacking the first substrate layer and the second substrate layer, the first substrate layer having a porosity of 50% to 85% and the second substrate layer having a porosity of 70% to 95% are stacked; Preferably, the second substrate layer is laminated on the first substrate layer by spinning, or the first substrate layer is laminated on the second substrate layer by spinning.

3. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The step of pressing the second solid electrolyte raw material into the porous structure of the second substrate layer specifically includes: The second solid electrolyte raw material is sprayed on the surface of the second substrate layer and filled.

4. The method for preparing a composite solid electrolyte membrane according to claim 3, characterized in that: The composite substrate layer is vibrated by a vibrating screen to perform filling; or, the composite substrate layer is lightly pressed by a sponge roller on one side of which the second solid electrolyte raw material is sprayed to perform filling.

5. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: Before the step of pressing the second solid electrolyte raw material into the porous structure of the second substrate layer, the method further comprises: The second solid electrolyte is mixed with a fiberizable binder and fiberized to prepare the second solid electrolyte raw material; Preferably, the second solid electrolyte and the fiberizable binder are mixed in a mass ratio of (99:1) to (99.9:0.1).

6. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: Before the step of pressing the first solid electrolyte raw material into the porous structure of the first substrate layer, the method further comprises: The composite substrate layer is turned over.

7. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The step of pressing the first solid electrolyte raw material into the porous structure of the first substrate layer specifically includes: Spraying a first solid electrolyte raw material on the surface of the first substrate layer and filling it; Preferably, a sponge roller is used to roll the composite substrate layer on one side of which the first solid electrolyte raw material is sprayed, for filling; the rolling pressure is 0.01 MPa to 5 MPa; Preferably, the particle size D50 of the first solid electrolyte is 1 μm to 5 μm.

8. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The step of pressing the second solid electrolyte raw material into the porous structure of the second substrate layer specifically includes: applying a pressing force to the surface of the composite substrate layer sprayed with the second solid electrolyte raw material, the pressing pressure is 2t to 3t; the pressing time is 30s to 5min; the pressing temperature is 60°C to 100°C; and / or, The step of pressing the first solid electrolyte raw material into the porous structure of the first substrate layer specifically includes: applying a pressing force to the surface of the composite substrate layer sprayed with the first solid electrolyte raw material, the pressing pressure is 2t to 3t; the pressing time is 30s to 5min; the pressing temperature is 60℃ to 100℃.

9. A composite solid electrolyte membrane, characterized in that: The composite solid electrolyte membrane is prepared by the preparation method according to any one of claims 1 to 8.

10. A solid-state battery, characterized in that: The solid-state battery comprises a positive electrode, a negative electrode and a composite solid electrolyte membrane as claimed in claim 9; Preferably, the first substrate layer faces the positive electrode of the electrochemical device, the second substrate layer faces the negative electrode of the electrochemical device, and the second solid electrolyte has better reduction resistance than the first solid electrolyte.